Effect of Helicobacter pylori infection and acid blockade by lansoprazole on clarithromycin bioavailability - Ortiz,R.A.M. (2007)
The effect of proton pump inhibitors and Helicobacter pylori infection on the bioavailability of antibiotics is poorly understood. We determined the effects of 5-day oral administration of 60 mg lansoprazole on the bioavailability of clarithromycin in individuals with and without H. pylori infection. Thirteen H. pylori-infected and 10 non-infected healthy volunteers were enrolled in a study with an open-randomized two-period crossover design and a 21-day washout period between phases. Plasma concentrations of clarithromycin in subjects with and without lansoprazole pre-treatment were measured by liquid chromatography coupled to a tandem mass spectrometer. Clarithromycin Cmax and AUC0-10 h were significantly reduced after lansoprazole administration. In addition, lansoprazole treatment of the H. pylori-positive group resulted in a statistically significant greater reduction in Cmax (40 vs 15%) and AUC0-10 h (30 vs 10%) compared to lansoprazole-treated H. pylori-negative subjects. Thus, treatment with lansoprazole for 5 days reduced bioavailability of clarithromycin, irrespective of H. pylori status. This reduction, however, was even more pronounced in H. pylori-infected individuals.